Penerapan Permainan Congklak Tray Ceria (Traycer) untuk Meningkatkan Kemampuan Konsep Membilang di KB Nice Kids Malang - Isnaini Mukarromah; Ayu Asmah; Mochammad Ramli Akbar (Universitas Nusantara PGRI Kediri, 2026)
Counting is an important skill for early childhood cognitive development. This counting skill includes understanding the number of objects, the ability to identify and sequence numbers correctly. The results of initial observations conducted at the Nice Kids Malang Kindergarten showed that children's number concept abilities were still low at 35%. This study aimed to investigate the application of the Congklak Traycer game in improving number concept abilities at the Nice Kids Malang Kindergarten Kindergarten. The method used in this study was a classroom action that was carried out in cycles, through the stages of planning, action implementation, observation, and reflection. The subjects of this study consisted of 10 children aged 4-5 years. Data collection in this study utilized an observation sheet that included indicators of number concepts, number symbols, one-to-one correspondence, and cardinality. Data analysis utilized a quantitative descriptive approach. The study findings showed a gradual increase in number concept abilities. In the pre-action stage, 35% increased to 45% in cycle I, and increased significantly to 82.48% in cycle II. Based on the classical success criteria in cycle II, exceeding the completion indicator of >75%, 8 out of 10 children were able to master the concepts of counting, number symbols, one-to-one correspondence, and cardinality very well. It can be concluded that game-based learning with concrete media through cheerful congklak trays (traycers) has been proven to help improve the conceptual ability of counting in early childhood at KB Nice Kids Malang. In addition, further research is needed to demonstrate the effectiveness of this method on a larger sample, as well as to develop innovative and fun teaching materials.